Fire coral persistent cutaneous reaction - Paradisi, M... (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2001)
A patient who developed a persistent cutaneous reaction to fire coral is presented. Treatment with topical corticosteroids reduced the severity of the lesion but after a folloe-up period of 18 months no complete resolution has been showed.
Keywords: Adult; Chemically induced; Cnidaria; Cnidarian venoms; dermatologija; Drug therapy; korale; kožne spremembe; ožigalkarji; Skin diseases